Reduction of Neuroinflammation by δ-Opioids Via STAT3-Dependent Pathway in Chronic Glaucoma Model - Husain, Shahid; Zaidi, Syed A. H.; Singh, Sudha; Guzman, Wendy; Mehrotra, Shikhar (Frontiers in Pharmacology, 2021)
The main objective of this study was to determine the inhibition of pro-inflammatory cytokines and their associated signaling molecules by δ-opioid receptor activation by a selective ligand, SNC-121 in chronic rat glaucoma model. Intraocular pressure was raised in rat eyes by injecting 2M hypertonic saline into the limbal veins. SNC-121 (1 mg/kg; i.p) or Stattic (5 mg/kg; i.p) was administered in Brown Norway rats daily for 7 days. Retinas were collected at day 7, post injury. The changes in the cytokines mRNA and protein and posttranslational modifications (e.g., phosphorylation and acetylation of STAT3) were measured by quantitative RT-PCR, Western blotting, and Immunohistochemistry. The mRNA expression of IL-1β, TNF-α, Fas, IL-6, LIF, and IFN-γ was increased significantly in the retina of ocular hypertensive animals at day 7, post injury. Administration of SNC-121 (1 mg/kg; i.p. injection) for 7 days (once a day) completely inhibited the increase in the mRNA and protein expression of pro-inflammatory cytokines. Mechanistically, we provide data showing a significant increase in the phosphorylation of STAT3 at tyrosine 705 whereas a moderate but significant increase in the total STAT3 protein expression was also seen in the retina of ocular hypertensive animals. Data illustrated that SNC-121 administration completely abrogated ocular hypertension-induced increase in STAT3Y705 phosphorylation. Interestingly, acetylation of STAT3 at lysine 685 (AcK685) was also increased significantly by SNC-121 treatment in ocular hypertensive animals. Stattic, a selective STAT3 inhibitor, administration resulted in a complete attenuation in the production of IL-1β and IL-6 in ocular hypertensive animals whereas it had a marginal inhibitory effects on TNF-α and IFN-γ production. In conclusion, δ-opioid receptor activation suppressed the phosphorylation of STAT3 at tyrosine 705 and increased acetylation at lysine 686 and these posttranslational modifications can regulate the production of some but not all pro-inflammatory cytokines in response to glaucomatous injury.